Diagnosis of Abdominal Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at the Children's Hospital of the King's Daughters, Norfolk, VA conducted a retrospective chart review on patients referred with the clinical complaint of recurrent abdominal pain, and ICHD-2 criteria were applied to identify those fulfilling criteria for abdominal migraine (AM).